Development of Instrumented Cane for Control of Exoskeleton of Lower Limb - Selvathurai, Govindarajoo (Universiti Teknologi PETRONAS, 2016)
Instrumented Cane is a wearable sensory system for patient’s motion intention estimation in order to control the trajectory of lower limb exoskeleton. This Instrumented Cane will be a helpful assistive device in term of balance and mobility for those who suffering neurological condition, in particular cerebrovascular accidents and spinal cord injury. This report describes the study on system utilizing Instrumented Cane as a feasible interface between the patient and exoskeleton to improve in term of mobility in their day-to-day activities. The system is designed with inertial measurement unit integrated with wireless communication module in order to assist real-time control of exoskeleton. This report strives the purpose of an Instrumented Cane that able to contribute to the assisted locomotion technology as well as improves the mobility of physically challenged people.